TO ASSESS THE FEATURES OF HEROISM AND SUBLIMITY IN CHOPIN’S SCHERZO MUSIC FOR EDUCATION PURPOSE - Na Ma; Weibo Dang (Fonseca, Journal of Communication, 2024)
Over the course of his life, Chopin wrote four scherzos that include a wide range of emotions and moods, including humor, tragedy, sublimity, dignity, and humor. In these four pieces, the scherzo is elevated to a higher artistic plane, free of sensationalism and ugliness. Additionally, by using humor, they elevate the genre’s intellectual and philosophical depth. To sum up, Chopin’s scherzos are characterized by valor and sublimity. He sees heroes in his heart as more than just flawless mythological figures removed from everyday life; he has given them additional romantic hues. Their vulnerability, expectation, desperation, and effort have transformed them into humanized romantic heroes. If public heroes can’t discover their true home and find solace and strength there, they will lose power and may even die. Their courageous fighting ability can only be sustained in this manner.